Implementasi Model Problem Based Learning Untuk Meningkatkan Proses Pembelajaran Tematik Terpadu Dikelas V SD - Islami, Rahmadanil; Zuryanty, Zuryanty (Universitas Negeri Padang, 2022)
This study aims to describe the increase of the learning process by using the Problem Based Learning model on integrated thematic learning. This type of research is classroom action research using qualitative and quantitative approaches. The study was conducted at SDN 22 Ujung Gurun Padang city. The results of the study aimed: (1) The evaluation of learning plans in cycle I was 79.16% (good) then increased to 97.2% (very good) in cycle II. (2) Observations on the aspect of teacher cycle I with a percentage of 81.24% (good) increased in cycle II to 95.83% (very good). (3) Aspects of cycle I students with a percentage of 81.24% (good) increased in cycle II to 95.83% (very good). It can be concluded that the problem based learning model can improve the integrated thematic learning process in elementary schools.